Leveraging AI and Deep Learning for Predictive Rail Infrastructure Maintenance: Enhancing Safety and Reducing Downtime (International Journal of Engineering and Computer Science, 2024)
The rapid advancement of artificial intelligence (AI) and deep learning technologies offers significant opportunities to enhance predictive maintenance strategies within the rail infrastructure sector. This paper explores the integration of AI-driven methodologies to forecast maintenance needs, thereby improving safety and minimizing operational downtime. We present a comprehensive framework that utilizes machine learning algorithms to analyze large datasets from sensors, historical maintenance records, and operational metrics. By identifying patterns and predicting potential failures before they occur, our approach not only optimizes maintenance schedules but also extends the lifespan of rail assets. Case studies demonstrate the efficacy of these techniques in real-world scenarios, highlighting reduced costs, enhanced safety measures, and improved service reliability. The findings underscore the transformative potential of leveraging AI and deep learning in revolutionizing rail infrastructure management, paving the way for smarter, more resilient rail systems.